THE ANATOMY OF RUSSIAN THE TIME OF TROUBLES - P. L. Karabushchenko (Современная наука и инновации)
In its history, Russia has experienced two great turmoil (the beginning of XVII and XX centuries), and a lot of smaller sociopolitical upheavals which degrees shook the its political and social foundations, forcing the authorities and society to find new compromises, a balance of power, other forms of joint common life.